On the powers of quasihomogeneous Toeplitz operators - Aissa, Bouhali (2021)
In this article, a fixed point iterative scheme involving Green's function is applied to reach a solution for the buckling of nano-actuators under nonlinear forces. Our solution is convergent. The nano-actuators problem under consideration is governed by a general type equation that contains nonlinear forces and integro-differential terms. The equation, we adopted and which governs the nano-actuators, is a nonlinear integro-differential BVP of fourth order. Our scheme enjoys important features such as high accuracy, robustness, and fast convergence. Numerical tests are performed and compared with other results that exist in the current literature.